Design and verification of model predictive control for micro-turboshaft engine. (December 2019) - Zhang, Mengwei; Lin, Zhixiang; Huang, Haiyang; Zhang, Tianhong
In this article, a nonlinear model predictive control algorithm for a micro-turboshaft engine is designed. The control effect is verified by a bench test. First, a micro-turboshaft engine test bench is built, and the open-loop control experiment was carried out on it. Based on experiment data, a linear parameter varying prediction model is established. Then, by online rolling optimization based on multistep output prediction, together with feedback correction, a nonlinear model predictive control algorithm is obtained. The influence of algorithm parameters on the control effect is studied, and reasonable prediction period M, control period N, and control coefficient R are designed. Finally, the application of nonlinear model predictive control in micro-turboshaft engine is verified by bench test. The results show that with the changing of pitch angle, nonlinear model predictive control algorithm has a faster adjustment speed and smaller overshoot, compared with the conventional cascade proportional–integral control with feedforward. It is proofed that nonlinear model predictive control can be applied to a real turboshaft engine and has a better control effect.